Prescription of Anticholinergics in Tardive Syndromes: A “Dual Center” Survey among Psychiatrists - Anna Cutino; Roongroj Bhidayasiri; Carlo Colosimo (Parkinson's Disease)
Background and Objectives. Anticholinergics have been proposed in the therapy of tardive syndromes since the early 60 s, despite only anecdotal reports of a positive effect and a lack of sound evidence supporting their usefulness. Methods. We assessed the attitude of two groups of psychiatrists (practicing in Italy and Thailand) towards the prescription of anticholinergics by a short online survey consisting of four questions. A total of one hundred questionnaires were sent out (50 in Italy and 50 in Thailand), and 42 psychiatrists responded to the survey. Results. When comparing the two cohorts, the difference, both for age and years of practice, was statistically significant (p<0.00001 and p<0.0001, respectively), with Thai psychiatrists being younger and with less time in practice as specialists. The results from the survey showed that the prescription of anticholinergic drugs at the beginning of the antipsychotic treatment was used by 5 psychiatrists (20.0%) of the Italian cohort and by 1 (5.9%) of the Thai cohort. Regarding the Italian psychiatrists who did not prescribe anticholinergics concomitantly with neuroleptics, we found that 5 (25.0%) of them had prescribed anticholinergics in the past but had abandoned this practice, while 15 (93.7%) of the Thai psychiatrists who did not prescribe anticholinergics at the moment of the survey answered that they had prescribed these drugs in the past. Conclusion. According to this preliminary survey, the practice to use anticholinergics as a treatment for tardive syndromes is still relatively common, particularly in psychiatrists of the older generation, but seemingly in decline over the years.